Effect of radiotherapy on brain glucose metabolism in patients operated on for low grade astrocytoma. Issue 5 (1st May 1999) - Bruehlmeier, M; Roelcke, U; Amsler, B; Schubert, K H; Hausmann, O; von Ammon, K; Radü, E W; Gratzl, O; Landmann, C; Leenders, K L
Abstract : OBJECTIVE: To assess the effect of postoperative radiotherapy on brain glucose metabolism (CMRGlu) of operated patients with low grade astrocytomas. METHODS: PET and 18 F-fluorodeoxyglucose was used to measure absolute CMRGlu in patients with fibrillary astrocytoma (WHO II) of the frontal lobe, who did (n=7) or did not (n=12) receive radiotherapy subsequent to first debulking tumour resection. In addition, statistical parametric mapping (SPM95) was applied to assess the pattern of relative CMRGlu associated with the frontal tumour. Data were compared with 12 healthy controls. RESULTS: A global reduction of absolute CMRGlu was found when either patients with or without radiotherapy were compared with controls (ROI analysis). Brain areas of relative CMRGlu reduction were found in the brain ipsilateral and contralateral to the tumour, comparing both patient groups with controls by SPM ("tumour diaschisis effect"). Superimposed, absolute CMRGlu in the contralateral frontal, parietal, occipital cortex as well as in the white matter was on average 17% lower in patients receiving radiotherapy than in patients who did not. CONCLUSIONS: The data discriminate a tumour effect from a radiotherapy effect, and support the view of adverse effects of radiotherapy on brain not directly involved by tumour.